2010
DOI: 10.1007/s12185-010-0520-1
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells as source of dendritic cells for immune therapy

Abstract: Dendritic cells (DC) are the most potent antigen-presenting cells. In vivo transfer of antigen-bearing DC has proven efficient in priming T cell responses specific to the antigen. DC-based cellular vaccination is now regarded as a powerful means for immunotherapy, especially for anti-cancer immunotherapy. Clinical trials of therapy with DC pulsed with peptide antigens or genetically modified to present antigens are currently carried out in many institutions. In addition, antigen-specific negative regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Previous studies have established methods of generating DCs from PSCs, and demonstrated the utility of PSC-derived DCs in cancer immunotherapy (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, generating a large number of DCs from ESCs or iPSCs has required a scaling-up of the initial volume of undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established methods of generating DCs from PSCs, and demonstrated the utility of PSC-derived DCs in cancer immunotherapy (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, generating a large number of DCs from ESCs or iPSCs has required a scaling-up of the initial volume of undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…DC differentiation from hPSCs: promise and progress Similar to deriving HSCs, there are two methods for DC differentiation from hPSCs: (1) through the formation of EBs in suspension culture; and (2) by co-culture with mouse OP9 stromal cell line [54] . The differentiation into DCs starts from mesoderm specification induced by growth factors including vascular endothelial growth factor (VEGF) and bone morphogenetic protein (BMP)-4 ( Figure 2) [20,52] .…”
Section: Hpscs: a New Source For DCmentioning
confidence: 99%
“…Examples are auditory retinal cells (Jin et al 2009 ;Comyn et al 2010 ;Lamba et al 2010 ;Parameswaran et al 2010 ) , cardiomyocytes (Narazaki et al 2008 ;Pfannkuche et al 2009 ;Tanaka et al 2009 ;Zhang et al 2009b ;CarvajalVergara et al 2010 ;Kaichi et al 2010 ;Martinez-Fernandez et al 2010 ) , insulinsecreting islet-like clusters (Tateishi et al 2008 ) , motor neurons (Dimos et al 2008 ;Ebert et al 2009 ;Hu and Zhang 2009 ;Karumbayaram et al 2009 ) , dopaminergic neurons (Wernig et al 2008 ;Cai et al 2010 ;Swistowski et al 2010 ) , auditory spinal ganglion neurons (Nishimura et al 2009 ) , smooth muscle cells (Taura et al 2009b ;Xie et al 2009 ) , vascular endothelial cells (Taura et al 2009b ) , dendritic cells and macrophages (Senju et al 2009(Senju et al , 2010 , adipocytes (Tashiro et al 2009 ;Taura et al 2009a ) , osteoblasts (Tashiro et al 2009 ) , hematopoietic cells (Hanna et al 2007 ;Eminli et al 2009 ;Kaufman 2009 ;Lu et al 2009 ;Okabe et al 2009 ;Raya et al 2009 ;Kaneko et al 2010 ) , and endothelial progenitor cells (Xu et al 2009 ;Abaci et al 2010 ;…”
Section: Differentiation Of Obtained Ips Cells To Desired Cell Typesmentioning
confidence: 99%